2005
DOI: 10.1103/physrevd.72.035003
|View full text |Cite
|
Sign up to set email alerts
|

Solving the supersymmetricCPproblem with flavor breakingFterms

Abstract: Supersymmetric flavor models for the radiative generation of fermion masses offer an alternative way to solve the SUSY-CP problem. We assume that the supersymmetric theory is flavor and CP conserving. CP violating phases are associated to the vacuum expectation values of flavor violating susy-breaking fields. As a consequence, phases appear at tree level only in the soft supersymmetry breaking matrices. Using a U (2) flavor model as an example we show that it is possible to generate radiatively the first and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 217 publications
(121 reference statements)
0
20
0
1
Order By: Relevance
“…In view of this circumstance, we had to restrict ourselves from the outset to ad hoc simplified MSSM scenarios even for simpler observables in the tt and W + W − systems (see, for example, [32]), in which case reconstruction at colliders is possible. The explicit expressions for the MSSM contributions to the amplitudes of meson mixing in the class of models involving the radiative generation of fermion masses and a review of previous publications on the subject can be found in [33]. Possible constraints on the H ± mass and, accordingly, on the contributions of box diagrams involving exchanges of H ± have not been considered there.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of this circumstance, we had to restrict ourselves from the outset to ad hoc simplified MSSM scenarios even for simpler observables in the tt and W + W − systems (see, for example, [32]), in which case reconstruction at colliders is possible. The explicit expressions for the MSSM contributions to the amplitudes of meson mixing in the class of models involving the radiative generation of fermion masses and a review of previous publications on the subject can be found in [33]. Possible constraints on the H ± mass and, accordingly, on the contributions of box diagrams involving exchanges of H ± have not been considered there.…”
Section: Discussionmentioning
confidence: 99%
“…Possible constraints on the H ± mass and, accordingly, on the contributions of box diagrams involving exchanges of H ± have not been considered there. According to [33], the MSSM contributions increase strongly at unacceptably large values of about 40 to 50 for tanβ and a specific choice of phases and relations between the superpartner and gaugino masses. As was indicated above, a totally different situation in which the MSSM contributions can be suppressed by moving to the parameter-space region where tanβ takes moderate values and where the superpartner masses are degenerate has been considered in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The rich phenomenology for the THDM has been widely studied by different theoretical and phenomenological groups. Some reports show interesting results for the Flavor-changing (FC) [2][3][4], an analysis at one-loop level for the pseudoscalar appears in [5], and at two loops in the lepton sector is found in [6]. Several experimental reports are dedicated to the exotic physics searching for new particles coming from a variety of models [7-13].…”
Section: Introductionmentioning
confidence: 99%
“…2. Heavy masses of the first and second generation sfermions to solve the SUSY and CP flavor problems or at least to ameliorate them [81,82].…”
mentioning
confidence: 99%